Rotator cuff repair: A biomechanical ex vivo ovine study. (May 2013) - Bisbinas, Ilias; Magnissalis, Evangelos; Gigis, Ioannis; Beslikas, Theodoros; Hatzokos, Ippokratis; Christoforidis, Ioannis
The purpose of this study was to assess load to failure of sutures, suturing techniques, and suture anchors used in rotator cuff surgery in order to explore their weaknesses. Ten types of sutures (absorbable and nonabsorbable), four types of suturing techniques, and eight types of suture anchors (bioabsorbable and metallic) were tested. Material Testing Machine and attached load cell were used to test the biomaterials in ex vivo ovine tissues. The results show that the mean load to failure and stiffness were higher in nonabsorbable sutures. Massive cuff tear and modified Mason-Allen suturing techniques had higher failure strength and stiffness when compared to simple and mattress techniques, but there was no substantial difference between them. Metallic suture anchors had higher failure strength when compared to bioabsorbable ones. Often either in metallic or in bioabsorbable anchors, the eyelet fails first. The failure sequence in ovine tissues is found to be in the following order: simple and mattress suturing techniques, nonabsorbable sutures, massive cuff tear and modified Mason-Allen suturing techniques, bioabsorbable anchors, and metallic anchors. Thus, it is concluded that metallic anchors mounted with modern nonabsorbable sutures will fail last. If we use simple and mattress techniques, the tendon–suture level will fail first, but it will improve substantially using more sophisticated suturing techniques (massive cuff tear or modified Mason-Allen).